Ko Tae Mun, Ko Chung Hee, and the Osaka Family Origins of North Korean Successor Kim Jong Un - Kokita Kiyohito; Mark Selden; Tessa Morris-Suzuki (Asia-Pacific Journal, 2011)
The following article by Kokita Kiyohito, on the family origins of Kim Jong Un, the leader designate of North Korea, is illuminating above all for the language, assumptions and treatment of issues related to North Korea in contemporary Japanese media, including the Asahi. Two brief commentaries locate some of the issues in broader perspective. The headline and article are taken from the Asahi’s weekly Aera; photos have been provided from other sources. The major story addressed in the commentary by Tessa Morris-Suzuki is the collaboration of the Japanese government and the International Red Cross in arranging the migration of more than 93,000 Korean residents of Japan, who had been deprived of Japanese citizenship following Japan’s wartime defeat, to North Korea. Mark Selden examines a range of issues related to the perspective of the Japanese journalist on Zainichi Koreans and North Korea.